Users’ in-vivo: reference table on effects of ultrasound during pregnancy / Khairunnisa Abd Manan … [et al.] - Abd Manan, Khairunnisa; Md Dom, Sulaiman; Ahmad Zaiki, Farah Wahida; Saat, Nurul Hidayah (Research Innovation Business Unit, 2014)
Prenatal Ultrasound (US) is commonly used as a routine procedure on pregnant women. It is generally perceived as a safe procedure due to the use of non-ionising radiation. However, its interaction with biological tissue could cause adverse effects. Thermal effect resulting from ultrasound energy absorption could interfere in the cellular function of human body. Unnecessary ultrasound exposure may lead to escalation of intrauterine temperature that may interrupt with the foetal rapid cell growth and proliferation. As a result, significant damage to the developing foetus and birth defects may occur. This study was aimed to investigate the changes on few parameters of rabbits (in-vivo study) caused by prenatal ultrasound exposure. This research involved experimental model using pregnant New Zealand White Rabbit (Oryctolagus cuniculus) and exposing them to US exposures at different duration and gestational stages which, based on the interest. The fundamental features in this research are the animals and the ultrasound system. The selection of animals was based on its suitability to fit in the research plan in terms of cost and availability, consultation, generalization of the results, housing availability, husbandry expertise, natural vs. experimental study, the numbers needed, life span and age, size of animals etc. While the selection of ultrasound system was justified based on its technology specification that currently were applied in obstetrics and gynaecology department. Approval from the faculty was obtained on Jun 12, 2012 while research proposal was accepted with minor amendment from Faculty of Health Sciences on Feb 20, 2012. New Zealand White Rabbits (NZWR) which its scientific name was Oryctolagus cuniculus, is the animal model throughout the study. NZWR was selected based on its class where it was from the same class as human; mammals. The rabbit was chosen due to their medium size, which made them easy to handle and easy to keep besides that their docile nature make these rabbits, particularly easy to maintain, handle and restrain. Their un-pigmented ears which may facilitate repeated venous injections and bleeding. There were so many types of rabbits such as Angora, Lion Head, Holland Lop, French Lop, Jersey Wobley and Hotot. NZWR was chosen because there are more fertile and prolific , besides this type of rabbit promised us a bigger litter size and higher live birth rate, which are important characteristics in order for the research well being and accomplishment. NZWR were obtained from One Stop Rabbit Farm & Trading, which located in Bukit Badong, Ijok in Selangor. The farm was the closest rabbit farm from the laboratory in terms of delivery of services, advice, documentation and any emergence cases such as sickness and fatality. The order will be made at least two weeks prior to the delivery date so that the breeder can pick and quarantine the rabbits and thus the maximum care will take place in order to assure their health and general condition is good. During the quarantine session, any flaws will be taken care of, such as ringworm and diarrhoea. After the quarantine session end, they are delivered to their new home, which is an animal laboratory located in Faculty of Health Sciences, UiTM Puncak Alam. Based on the research, we found significant differences in the statistic value between the control and treated group.